Remote Tracking Gas Molecular via the Standalone-Like Nanosensor-Based Tele-Monitoring System - Jin, Han; Yu, Junkan; Cui, Daxiang; Gao, Shan; Yang, Hao; Zhang, Xiaowei; Hua, Changzhou; Cui, Shengsheng; Xue, Cuili; Zhang, Yuna; Zhou, Yuan; Liu, Bin; et al. (Nano-Micro Letters, 2021)
Remote tracking the variation of air quality in an effective way will be highly helpful to decrease the health risk of human short- and long-term exposures to air pollution. However, high power consumption and poor sensing performance remain the concerned issues, thereby limiting the scale-up in deploying air quality tracking networks. Herein, we report a standalone-like smart device that can remotely track the variation of air pollutants in a power-saving way. Brevity, the created smart device demonstrated satisfactory selectivity (against six kinds of representative exhaust gases or air pollutants), desirable response magnitude (164–100 ppm), and acceptable response/recovery rate (52.0/50.5 s), as well as linear response relationship to NO2. After aging for 2 weeks, the created device exhibited relatively stable sensing performance more than 3 months. Moreover, a photoluminescence-enhanced light fidelity (Li-Fi) telecommunication technique is proposed and the Li-Fi communication distance is significantly extended. Conclusively, our reported standalone-like smart device would sever as a powerful sensing platform to construct high-performance and low-power consumption air quality wireless sensor networks and to prevent air pollutant-induced diseases via a more effective and low-cost approach. Highlights: 1 A standalone-like smart device that can remotely track the variation of air pollutants in a power-saving way is created; 2 Metal–organic framework-derived hollow polyhedral ZnO was successfully synthesized, allowing the created smart device to be highly selective and to sensitively track the variation of NO2 concentration; 3 A novel photoluminescence-enhanced Li-Fi telecommunication technique is proposed, offering the created smart device with the capability of long distance wireless communication.